(3ebGdI aj EUdGM Tcd ef cJGH eGfGdGhS aj GdcQjGJ YOd ajg eUdMhG gPG GdcJGH Yf eTcdgs - (3efUhQ Hf Ydj Hf YQGb, CHh fUQ,J (B425 (3g` s
(3ChdgG (B:s
(3bGd CHhfUjQ (B: (3Efi cfJ CXf Cf GdeGgGfi GNJQY bHd EJeGe eG HJOCg ef EUdGM cJGH s
(3BNQgG (B:s
(3hdcfi Cfhi HEUdGM gPG GdcJGH HCSQg , aGdPi bOeJ gGgfG Ydi SHjd GdETGQI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B76(3W (B- (3U(B78(3hs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B474s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B472 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B88 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs